Clinical and biochemical profile of patients hospitalized with jaundice: Experience from a teaching hospital in north India - Chauhan, Suneel; Rana, Baldev S.; Sharma, Rajesh; Barwal, Vijay K.; Sood, Nikhil; Rana, Naveen; Minhas, Shailender; Chaudhary, Ankit (International Journal of Advances in Medicine, 2019)
Background: Jaundice is a common problem in both medical and surgical practice. For best line of management, it is very essential to differentiate all types of jaundice. The cause can often be correctly anticipated clinically but usually biochemical and radiological imaging investigations are required for confirmation. Here we present a study on clinical and biochemical profile of jaundice patients admitted in a tertiary care hospital. Methods: It was an observational study and all patients admitted with jaundice in the department of medicine meeting inclusion/exclusion criteria were enrolled. Data was collected on a self-designed, pretested and structured format. Results: Out of 100 patients, 77 were males, and median age of 47.5 years. Apart from jaundice, anorexia was the most common presenting complaint (90%), while ascites was the most common finding. Cirrhosis (60%) was the most common cause of jaundice. The mean total bilirubin was 7.9 mg%. Mean Hemoglobin in patients with cirrhosis was 9.7gm/dL. 78% patients of cirrhosis revealed esophageal varices. Majority (80%) showed hypoproteinemia. PT was prolonged >3sec in 87% of cases. On USG shrunken liver was noted in all patients with cirrhosis, enlarged liver was found in two patients of liver abscess while altered echotexture was seen in 66% cases. 90 patients improved, 9 died and only one was referred. Conclusions: Alcoholic liver disease was the leading cause of cirrhosis (92%). Jaundice in general and alcoholic cirrhosis in particular affects mostly the productive age group of the male population and has a high economic burden on our society.